Composition of fatty acids in Centaurea cyanus (L.) - Pietkova, I. B.; Unhurian, L. M.; Horiacha, L. M.; Kyslychenko, V. S.; Zhuravel, I. O.; Kuznietsova, V. Y.; Panasenko, О. I.; Панасенко, Олександр Іванович (My University, 2020)
The presented study shows the composition of fatty acids (FA) in fl owers and herb of wild and cultivated cornfl ower (Centaurea cyanus (L.)). The analysis was performed by gas chromatography (GC) with a method using internal normalization. Together 13 fatty acids were identifi ed in both types of cornfl ower herb. Unsaturated fatty acids, particularly, linoleic, linolenic, and oleic acids, were prevailing in cultivated cornfl ower fl owers and herb, as well as in wild cornfl ower fl owers. Palmitic acid was the most abundant saturated FA.
Keywords: Centaurea cyanus (L.); fatty acids; GC method